Association of BRCA Mutations and Anti-müllerian Hormone Level in Young Breast Cancer Patients - Son, Kyung-A; Lee, Dong-Yun; Choi, DooSeok (Frontiers in Endocrinology, 2019)
Background: Several preclinical and clinical studies have suggested that BRCA-mutation carriers may have decreased ovarian reserve. However, data in this area are limited and inconsistent, especially in young breast cancer patients. Objective: This study evaluated the association between BRCA mutation status and serum anti-Müllerian hormone (AMH) level in young, reproductive-aged patients with breast cancer. Materials and Methods: Patients ≤ 40 years of age with breast cancer and who had known BRCA status and baseline serum AMH level at Samsung Medical Center, Seoul, Korea, were considered for inclusion. A total of 52 BRCA mutation carriers (27 BRCA1 and 25 BRCA2) and 264 non-carriers were selected for analyses. The serum level of AMH was compared according to presence of a BRCA mutation, and linear and logistic regression analyses were performed to evaluate the association between BRCA mutation and serum AMH level. Results: No difference was found in clinical characteristics between BRCA-mutation carriers and non-carriers. Subjects with any BRCA mutation had a significantly lower median AMH than those without a mutation (2.60 vs. 3.85 ng/mL, 32% reduction, P=0.004). Linear regression analysis showed a significant negative association between BRCA mutation and AMH level. In addition, logistic regression demonstrated non-significantly increased odds of mutation carriers having AMH < 1.2 ng/mL. However, no difference was found between BRCA1/2 mutations. Conclusions: Breast cancer patients with BRCA mutation have significantly lower serum AMH level. Fertility preservation should be considered more aggressively in young breast cancer patients with BRCA mutation.